An investigation of dynamical metal transfer in GMAW : effects of argon shielding gas - Wong, Yoke-Rung (2013)
The unbalance radial electromagnetic force was firstly obtained by measuring the real-time input electrical impedance of GMAW. This force acts as an attaching force because it pushes the droplet aside of the welding wire and sticks on the tip of welding wire as result of surface tension force. In spray transfer mode, lower unbalance radial electromagnetic force was observed when argon shielding gas was used. The finding presented in this paper is contrary to the literature which reported that higher electromagnetic force is desirable for faster transfer rate of droplets in spray transfer mode.